Reducción de tasas de devolución en una empresa distribuidora con Lean Warehousing y RFID-WMS: Estudio de caso en el Perú - Ambicho Pinedo, Ricardo (2025)
This article examines a Peruvian company that distributes automotive supplies, which has consistently decreased in profits over the last five years of operation. This decline worsened in 2023, dropping by 34.33% compared to 2022. The downturn is attributed to reduced sales stemming from increased customer complaints and returns. Consequently, the company is compelled to take immediate actions to optimize warehouse management and enhance competitiveness. To address this, the study proposes the implementation of a Lean Warehousing model using tools such as cycle counting, min-max model, Systematic Layout Planning (SLP), ABC classification, standardized work, and RFID-WMS with IoT Shared Database to improve the order return indicator. Finally, a pilot test is employed to validate the model’s effectiveness, aiming to reduce the order return rate to 6.50%, thereby improving overall warehouse performance and avoiding significant profit reductions.